2021
DOI: 10.3384/rela.2000-7426.rela0058
|View full text |Cite
|
Sign up to set email alerts
|

Professionalisation and quality management

Abstract: The quality of adult educators is on the agenda of European educational policy and thescientific community in Europe. In these contexts, professionalisation and qualitymanagement are often conflated. This paper is based on the hypothesis that qualitymanagement and professionalisation follow two different approaches. The paperoutlines the two approaches with a focus on their two different logics. After a briefcomparison of the two approaches, the paper examines the conflation of these twoapproaches in the exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…From the policy context point of view, we can first observe that, as European adult education policy developed relatively late, endeavours aimed at ensuring greater professionalism on the part of adult educators in the European context started to develop with the EC's initiatives in 2006. These efforts reached a peak with the report on 'Key Competences for Adult Learning Professionals' in 2010, which some researchers (Egetenmeyer & K€ applinger, 2011) already recognised to serve as a basis for the EC conceptualisation of adult learning professionalism, as well this being reflected in documents of European adult education policy adopted latter on (CEU, 2011; 'Thematic Working Group on Quality in Adult Learning', 2013), which states that the quality of adult education staff should be based on (common) identified competence profiles. In this sense it might be argued, that identified key competences aimed to define professional standards for adult education professionals in Europe and suggested that member states use this outcomeled competency-based model as a 'frame of reference for improving or changing existing adult learning practices' (Research voor Beleid, 2010, p. 101).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the policy context point of view, we can first observe that, as European adult education policy developed relatively late, endeavours aimed at ensuring greater professionalism on the part of adult educators in the European context started to develop with the EC's initiatives in 2006. These efforts reached a peak with the report on 'Key Competences for Adult Learning Professionals' in 2010, which some researchers (Egetenmeyer & K€ applinger, 2011) already recognised to serve as a basis for the EC conceptualisation of adult learning professionalism, as well this being reflected in documents of European adult education policy adopted latter on (CEU, 2011; 'Thematic Working Group on Quality in Adult Learning', 2013), which states that the quality of adult education staff should be based on (common) identified competence profiles. In this sense it might be argued, that identified key competences aimed to define professional standards for adult education professionals in Europe and suggested that member states use this outcomeled competency-based model as a 'frame of reference for improving or changing existing adult learning practices' (Research voor Beleid, 2010, p. 101).…”
Section: Discussionmentioning
confidence: 99%
“…However, this conceptualisation of adult education professionalisation has been challenged by the research community in a variety of ways: (1) the proposed model has a strong economic focus and is based on a managerial perspective (Egetenmeyer & K€ applinger, 2011); 2competences identified through functional analysis only encompass what can be described and measured technically through job analysis, and by listing single tasks, the profession cannot be defined (Ju¨tte et al, 2011); 3the model does not distinguish between professionalisation as a process for developing the professionalism of people working in adult education as a field of practice 1 and quality management professionalisation, which targets adult education providers and their organisational development, the latter being understood as a reference point for the professionalisation of adult education (Egetenmeyer & K€ applinger, 2011); 4) the model positions adult educators as a unified group as well as 'not yet professional', i.e. diversity of practices in Europe is seen as a problem to be overcome through a professionalisation of the sector that can be achieved with standardisation and identification of the 'common elements' (Nicoll & Edwards, 2012, p. 237).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The importance of the cognitive component of a profession (a profession's specialised body of abstract, theoretical knowledge) has been stressed in many research studies that adopt traditional sociological approaches (Egetenmeyer and Käpplinger, 2018;Freidson, 1999;Ovesni, 2009). Some recent studies about the profession of employees and/or professionalisation in the field of AEL that adopted qualitative research methodology and explained this topic from the policy/system, institutional or individual perspectives have also stressed the importance of the cognitive component of the profession (Lattke, 2016;Egetenmeyer and Käpplinger, 2018). Moreover, the importance of this component has been emphasised in mixed methods research studies about the profession of employees in the field of AEL too (Eraut, 2000;Day and Gu, 2007).…”
Section: A Brief Outline Of Research Studies On Profession In the Field Of Aelmentioning
confidence: 99%
“…In this way, the qualification of those who carry out procedures in the field of adult education has received an increase of policy attention over the past decade (European Commission, 2006;European Commission, 2007;Research voor Beleid and PLATO, 2008;Research voor Beleid, 2010). Several authors have pointed out that the quality of work developed in adult education is dependent on the abilities and competences of the practitioners (Jütte, Nicoll and Olesen, 2011;Egetenmeyer and Käpplinger, 2011;Travers and Harris, 2014).…”
Section: Introductionmentioning
confidence: 99%